Luminescent materials with high exciton utilization and their applications
The existing OLED materials are solved by using a combination of dendributyriline derivatives and tris(triazole) triazine in OLED materials to construct a luminescent material with dual properties of hybrid local-charge transfer and thermal activity delayed fluorescence. The problem of low exciton utilization rate has achieved efficient and stable preparation of organic electroluminescent devices.
Patent Information
- Application Number
- CN202310073336.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-02-07
AI Technical Summary
Only 25% of excitons in existing OLED materials can be effectively utilized, resulting in 75% of the electrical energy being lost in the form of waste heat. How to develop efficient, stable, and low-cost pure organic electroluminescent materials to improve exciton utilization.
Using dendributylene derivatives as electron donors and tris(triazole) triazine as electron acceptors to construct a high exciton utilization luminescent material through covalent linkage to achieve hybrid local-charge transfer in the molecule and thermally active delayed fluorescence dual properties.
The OLED material with high exciton utilization rate has an external quantum efficiency of 11.96% and 9.9%. This material can be used as a luminescent material of the luminescent layer and as a sensitizer of the luminescent layer, and can be prepared efficiently by solution processing. Electroluminescent devices.
Smart Images

Figure QLYQS_1 
Figure BDA0004065456960000021 
Figure BDA0004065456960000022
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic electroluminescent materials, and particularly relates to a luminescent material with high exciton utilization rate and application thereof. Background Art
[0002] Organic light-emitting diodes (OLEDs) have very important applications in many fields such as display and lighting. Therefore, how to obtain efficient OLED devices is an urgent problem to be solved in the field of organic optoelectronics. OLEDs can convert injected current into excitons and emit light effectively. According to spin statistics theory, the ratio of triplet excitons to singlet excitons is 3:1, which means that in traditional fluorescent OLED devices, only 25% of the excitons can be effectively utilized, and the remaining 75% of the electrical energy is lost in the form of waste heat. Therefore, the development of a new generation of efficient, stable, and low-cost pure organic electroluminescent materials is particularly important for promoting the long-term sustainable development of the OLEDs industry.
[0003] At present, there are two main types of efficient OLEDs materials. The Adachi research group first applied thermally activated delayed fluorescence (TADF) materials to organic light-emitting diodes (OLEDs). Compared with traditional phosphorescent materials containing precious metals (such as Pt and Ir), TADF materials do not require precious metals and can theoretically achieve 100% internal quantum efficiency, which is conducive to reducing the cost of material preparation. Professor Ma Yuguang and others proposed a hot exciton material with high-energy triplet antisystem crossing characteristics, which achieved 100% exciton utilization through the high-energy triplet antisystem crossing process. It mainly regulates the excited state properties through the structural combination of donors and acceptors containing heteroatoms to meet the excited state properties required by the hot exciton process. The two materials are of great significance to the development of OLEDs materials. Existing DA-type luminescent materials based on tris(triazole) and triazine units all show thermally activated delayed fluorescence (TADF) properties or "hot exciton" (HLCT) properties. How to attribute the two properties to the same molecule and obtain OLEDs materials with high exciton utilization is of great significance to organic electroluminescent devices. Summary of the invention
[0004] In order to obtain OLEDs materials with high exciton utilization, the present invention provides a luminescent material with high exciton utilization using a dendritic triphenylamine derivative as an electron donor and tris(triazole)triazine as an electron acceptor. Due to the appropriate degree of charge transfer and orbital separation, the dual properties of intramolecular hybrid local and charge-transfer (HLCT) and thermal activation delayed fluorescence (TADF) are obtained. At the same time, the present invention also systematically studies the influence of the electron donor of the dendritic triphenylamine derivative on the material photophysical properties of the electron acceptor, which is of great significance for exploring efficient OLEDs materials.
[0005] In order to achieve the above technical objectives, the present invention uses a dendritic triphenylamine derivative as an electron donor and tris(triazole)triazine as an electron acceptor. The donor and the acceptor are covalently linked at the para position of the acceptor to synthesize a type of luminescent material with high exciton utilization. The material has the following structure:
[0006]
[0007] Wherein, R is hydrogen or tert-butyl ( t Bu), the structures of compound 1 and compound 2 are:
[0008]
[0009] The light-emitting material with high exciton utilization rate of the present invention obtains the dual properties of HLCT and TADF due to the appropriate degree of charge transfer and orbital separation.
[0010] Another object of the present invention is to provide an application of a luminescent material with high exciton utilization rate, wherein such a high exciton luminescent material based on tris(triazole)triazine as an acceptor is used as a dopant for a luminescent layer, and an organic electroluminescent device is prepared by solution processing.
[0011] In one embodiment of the present invention, mCP is used as the main material of the light-emitting layer, and compound 1 or compound 2 is used as the guest material (doping amount is 20wt%), and a green light device is obtained, and its external quantum efficiency is 11.96% and 9.9% respectively.
[0012] In another embodiment of the present invention, mCP is used as the main material of the light-emitting layer, compound 2 is used as a sensitizer (doping amount is 30wt%), and 5% of different phosphorescent materials (green BN4, orange PO-01, red Ir(piq)2acac) are doped to obtain solution-processed devices with external quantum efficiencies of up to 30.88%, 24.08% and 14.33% for green light, orange light and red light, respectively.
[0013] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0014] 1. The luminescent materials based on tris(triazole)triazine units reported so far are all luminescent materials with a single property of thermally activated delayed fluorescence (TADF) or thermoexcitons. The present invention uses a dendritic triphenylamine derivative as an electron donor and tris(triazole)triazine as an electron acceptor, introduces an acceptor with moderate electron-withdrawing ability and a donor with moderate electron-donating ability into the molecule to construct an intramolecular charge transfer state, and obtains the dual properties of HLCT and TADF with an appropriate degree of charge transfer and orbital separation, thereby obtaining a new type of green light luminescent material with high exciton utilization, which is completely different from the thermally activated delayed fluorescence or thermoexcitons reported so far;
[0015] 2. Due to the dual properties of this type of high-exciton luminescent material based on tris(triazole)triazine, it can be used as both a luminescent material for the luminescent layer and a sensitizer for the luminescent layer. Through solution processing, an organic electroluminescent device with high external quantum efficiency can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The compounds TTT-3TPA-H and TTT-3TPA- t Thermogravimetric curve of Bu;
[0017] Figure 2 The compounds TTT-3TPA-H and TTT-3TPA- t UV-visible absorption and photoluminescence spectra of Bu in toluene solution;
[0018] Figure 3 The photoluminescence spectra of the compound TTT-3TPA-H prepared in Example 1 of the present invention in triethylamine, cyclohexane, petroleum ether, 1,4-dioxane, toluene, ether, ethyl acetate, chloroform, N,N-dimethylformamide and dichloromethane solutions;
[0019] Figure 4 For the embodiment of the present invention TTT-3TPA- t Photoluminescence spectra of the compounds prepared by Bu in cyclohexane, petroleum ether, toluene, 1,4-dioxane, ether, ethyl acetate, chloroform, N,N-dimethylformamide and dichloromethane solutions;
[0020] Figure 5 This is a graph showing the instantaneous lifetime of the compound TTT-3TPA-H prepared in Example 1 of the present invention in a 10% doped PMMA film;
[0021] Figure 6The compound TTT-3TPA- prepared in Example 1 of the present invention t Instantaneous lifetime curve of Bu in 10% doped PMMA film;
[0022] Figure 7 This is a graph showing the relationship between the Stokes shift of the compound TTT-3TPA-H prepared in Example 1 of the present invention and the solvent polarity parameter;
[0023] Figure 8 The compound TTT-3TPA- prepared in Example 1 of the present invention t The relationship between the Stokes shift of Bu and the solvent polarity parameter;
[0024] Fig. 9 This is a relationship diagram between the current density and the maximum external quantum efficiency of the organic electroluminescent device prepared in Example 7 of the present invention;
[0025] Fig.10 This is an electroluminescence spectrum of the organic electroluminescent device prepared in Example 7 of the present invention;
[0026] Fig.11 This is a structural diagram of an organic electroluminescent device prepared in Example 9 of the present invention;
[0027] Fig.12 This is an efficiency spectrum diagram of the organic electroluminescent device prepared in Example 9 of the present invention. DETAILED DESCRIPTION
[0028] The following specific implementation cases are intended to further illustrate the present invention, but these specific implementation cases do not limit the protection scope of the present invention in any way.
[0029] Example 1
[0030] The synthesis scheme of the luminescent material with high exciton utilization rate based on tris(triazole)triazine of the present invention is as follows:
[0031]
[0032] Synthesis of compound SM1
[0033] Bis(4-bromophenyl)amine (6.2eq), 4-(N,N-dimethylamino)pyridine (1.22eq), di-tert-butyl dicarbonate (9.17eq) and tetrahydrofuran were added to a round-bottom flask. The mixture was heated to reflux for 3 hours under nitrogen protection. After cooling to room temperature, the mixture was poured into water and extracted with CH2Cl2. The organic layer was washed with water, dried over anhydrous MgSO4, evaporated to dryness, and column chromatography was performed to obtain a white solid with a yield of 55%. 1H NMR (400MHz, CDCl3) δ7.82 (s, 1H), 7.43 (d, J = 18.7Hz, 4H), 7.12 (d, J = 8.5Hz, 3H), 1.43 (s, 9H).
[0034] Synthesis of compound SM2
[0035] SM1 (1 eq.), diphenylamine (3 eq.), sodium tert-butoxide (4 eq.), tris(dibenzylideneacetone)dipalladium (0.06 eq.), tri-tert-butylphosphine tetrafluoroborate (0.12 eq.) and toluene were added to a round-bottom flask. The mixture was stirred at 120°C for 24 hours under nitrogen. After cooling to room temperature, the mixture was poured into water and extracted with CH2Cl2. The organic layer was washed with water, dried over anhydrous MgSO4, evaporated to dryness, and column chromatography was performed to obtain a white solid with a yield of 47%. 1H NMR (400 MHz, DMSO) δ 7.30 (s, 8H), 7.14 (s, 4H), 6.98 (d, J = 17.5 Hz, 16H), 1.38 (s, 9H).
[0036] Synthesis of compound SM3
[0037] SM2 (2.76 eq), trifluoroacetic acid (0.13 eq) and acetone were added to a round-bottom flask and stirred overnight at room temperature under nitrogen protection. After the reaction was completed, the mixture was poured into water and extracted with CH2Cl2. The organic layer was washed with water, dried over anhydrous MgSO4, evaporated to dryness, and column chromatography was performed to obtain a white solid with a yield of 49%. 1H NMR (400 MHz, DMSO) δ7.24 (s, 11H), 6.97 (d, J=8.2 Hz, 18H).
[0038] Synthesis of compound SM4
[0039] A mixture of 5-(4-bromobenzene)-2-hydrogen-tetrazolyl (4 eq), potassium carbonate (10 eq), cyanuric chloride (1 eq) and 50 mL of 2-butanone was heated to 90°C and stirred in air for 48 hours. After cooling to room temperature, the mixture was poured into water and extracted with dichloromethane. The organic layer was collected and washed with water and dried over anhydrous MgSO4. Evaporation to dryness and column chromatography gave a white solid. Yield 45%. 1H NMR (300MHz, CDCl3, TMS) δ (ppm) 8.05 (d, J = 9.0 Hz, 6H), 7.76 (d, J = 9.0 Hz, 6H).
[0040] Synthesis of Compound 1(R1)
[0041]
[0042] SM4 (1 eq.), SM3 (5 eq.), sodium tert-butoxide (4 eq.), tris(dibenzylideneacetone)dipalladium (0.06 eq.), tri-tert-butylphosphine tetrafluoroborate (0.12 eq.) and toluene were added to a round-bottom flask. The mixture was stirred at 120°C for 24 hours under nitrogen. After cooling to room temperature, the mixture was poured into water and extracted with CH2Cl2. The organic layer was washed with water, dried over anhydrous MgSO4, evaporated to dryness, and column chromatography was performed to obtain a green solid. Yield 35%. 1H NMR (400 MHz, CDCl3) δ 8.02 (s, 6H), 7.37 (d, J = 18.7 Hz, 6H), 7.18 (d, J = 8.5 Hz, 84H).
[0043] Synthesis of compound 2 (R2)
[0044]
[0045] SM4 (1 eq.), SM3 (5 eq.), sodium tert-butoxide (4 eq.), tris(dibenzylideneacetone)dipalladium (0.06 eq.), tri-tert-butylphosphine tetrafluoroborate (0.12 eq.) and toluene were added to a round-bottom flask. The mixture was stirred at 120°C for 24 hours under nitrogen. After cooling to room temperature, the mixture was poured into water and extracted with CH2Cl2. The organic layer was washed with water, dried over anhydrous MgSO4, evaporated to dryness, and column chromatography was performed to obtain a green solid. Yield 26%. 1H NMR (400 MHz, CDCl3) δ 8.01 (s, 6H), 7.37 (d, J = 18.7 Hz, 6H), 7.02 (d, J = 8.5 Hz, 72H), 1.33 (s, 108H).
[0046] Example 2
[0047] Compounds 1 and 2 in Example 1 were heated at a rate of 20°C per minute in the range of 50-600°C under N2, and thermogravimetric curves were measured. Figure 1 It can be seen that the 5% decomposition temperatures of compounds 1 and 2 are 345°C and 423°C, respectively.
[0048] Example 3
[0049] Compounds 1 and 2 in Example 1 were dissolved in toluene to prepare 10 -5 M solution, and test its UV-visible absorption and photoluminescence spectrum. Figure 2 It can be seen that the UV-visible absorption spectrum of the compound in solution has roughly two absorption peaks: the absorption peak at short wavelength (306nm) is mainly attributed to the π-π* transition absorption of the molecule; the absorption peak at long wavelength (340nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit in the molecule. Figure 2 As shown, the maximum emission peak of compound 1 is 527 nm, and the emission peak of compound 2 is 537 nm, indicating that both compounds are in the green light emission region.
[0050] Example 4
[0051] The photoluminescence properties of compounds 1 and 2 in Example 1 were tested in different solutions. Compound 1 was dissolved in triethylamine, cyclohexane, petroleum ether, 1,4-dioxane, toluene, ether, ethyl acetate, chloroform, N,N-dimethylformamide and dichloromethane solutions, and compound 2 was dissolved in cyclohexane, petroleum ether, toluene, 1,4-dioxane, ether, ethyl acetate, chloroform, N,N-dimethylformamide and dichloromethane solutions, and their photoluminescence spectra in different solutions were tested, as shown in FIG. Figure 3 , 4 As shown in Figure 2, with the increase of solvent polarity, both compounds exhibited obvious solvatochromism, which is a typical sign of the CT characteristics of the corresponding excited state molecules. In addition, compared with the dichloromethane solution, the maximum red shift of compound 1 in cyclohexane solution was 78nm, and the maximum red shift of compound 2 was 72nm.
[0052] Example 5
[0053] The fluorescence lifetime of compounds 1 and 2 in Example 1 in a 10% doped PMMA film was tested under a nitrogen atmosphere. Figure 5 , 6 As shown, after fitting, it was found that the delayed lifetimes of the two compounds were 3.6ns and 2.9ns, respectively, both of which were short lifetimes.
[0054] Example 6
[0055] The relationship between the Stokes shift and the solvent polarity parameter of compounds 1 and 2 in Example 1 according to the Lippert-Mataga solvatochromic model is shown in FIG. Figure 7 , 8 As shown, all compounds exhibit two linear fits in low-polarity solvents and high-polarity solvents, respectively, indicating the existence of two different excited states.
[0056] Example 7
[0057] The application of compounds 1 and 2 in Example 1 in organic electroluminescent devices. An organic electroluminescent diode with a structure of ITO / PEDOT:PSS(40nm) / mCP:(20wt%)Guest / TmPyPB(45nm) / LiF(0.5nm) / Al(120nm) was prepared using the compounds as dopants in the light-emitting layer of the device. Among them, PEDOT:PSS is the hole injection layer, mCP is the main material of the light-emitting layer, TmPyPB is the electron transport layer, LiF is the electron injection layer, and Al is the cathode. Among them, the maximum external quantum efficiencies of compounds 1 and 2 in the 20wt% doped device are 11.96% and 9.9%, respectively. Fig. 9 shown.
[0058] Example 8
[0059] The electroluminescence spectra of compounds 1 and 2 in the organic electroluminescent device in Example 1. Fig.10 As shown, both compounds exhibit green light emission in a 20 wt % doped device, and the emission peaks of compound 1 and compound 2 are at 502 nm and 506 nm, respectively.
[0060] Example 9
[0061] Using compound 2 in Example 1 as a sensitizer, a sensitizer having a structure of ITO / PEDOT:PSS(35nm) / mCP:30wt% TTT-3TPA- t Device of Bu:5wt% dopant (30nm) / Bis[2-(diphenylphosphino)phenyl]etheroxide (DPEPO) (6nm) / TmPyPB (45nm) / LiF (1nm) / Al (120nm), where 5wt% dopant refers to green light material doped with 5wt%
[0062] BN4 or orange light material PO-01 or red light material Ir(piq)2(acac) have achieved external quantum efficiencies up to
[0063] Solution-processed devices with green, orange and red light of 30.88%, 24.08% and 14.33% respectively.
Claims
1. A luminescent material with high exciton utilization rate, characterized in that: The light-emitting material with high exciton utilization rate uses a dendritic triphenylamine derivative as an electron donor and tris(triazole)triazine as an electron acceptor. The donor and the acceptor are covalently linked at the para position of the acceptor. The molecular structure is shown in Formula I: , Wherein, R is hydrogen or tert-butyl, and the R groups are the same.
2. The light-emitting material with high exciton utilization rate according to claim 1, characterized in that: The light-emitting material with high exciton utilization rate has intramolecular hybridization localization-charge transfer properties and thermally active delayed fluorescence properties.
3. The use of the luminescent material with high exciton utilization rate according to claim 1 or 2, characterized in that: An organic electroluminescent device is prepared by solution processing using a luminescent material with high exciton utilization rate as a luminescent layer dopant.
4. The use of the luminescent material with high exciton utilization rate according to claim 3, characterized in that: The luminescent material with high exciton utilization rate is used as the guest material of the luminescent layer, and its doping amount is 20 wt %, and the obtained organic electroluminescent device is a green light device.
5. The use of the luminescent material with high exciton utilization rate according to claim 3, characterized in that: The luminescent material with high exciton utilization rate is used as a sensitizer, and its doping amount is 30%, so as to obtain a solution-processed device of green light, orange light and red light.
Citation Information
Patent Citations
Thermal activation delayed fluorescence material and application thereof
CN111393448A
Dark blue heat exciton luminescent material as well as preparation method and application thereof
CN114195796A